2021
DOI: 10.1155/2021/5130586
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Hepatitis A and Hepatitis E Viruses among Pregnant Women in Northern Iran

Abstract: Background. Hepatitis A (HAV) and hepatitis E viruses (HEV) are endemic in Iran and are known major causes of acute viral hepatitis. Also, during pregnancy, they are associated with severe outcomes. Therefore, it is vital to evaluate the antibody levels against HAV and HEV in pregnant women to avoid severe outcomes incidence. Study design and methods. A total of 247 pregnant women were enrolled in this prospective cross-sectional study. In addition to completing the questionnaire and interviewing all participa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Our findings showed that the seroprevalence of HEV infection in ME countries ranged from 0.8% among Iranian pregnant women [ 88 ] to 84.3% among Egyptian pregnant women [ 37 ]. Different test methodologies and geographic locations, research sample size, surveillance year, and other factors could explain these observed differences in HEV seroprevalence.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings showed that the seroprevalence of HEV infection in ME countries ranged from 0.8% among Iranian pregnant women [ 88 ] to 84.3% among Egyptian pregnant women [ 37 ]. Different test methodologies and geographic locations, research sample size, surveillance year, and other factors could explain these observed differences in HEV seroprevalence.…”
Section: Discussionmentioning
confidence: 99%